PERAWATAN KELUARGA PADA LANSIA PENDERITA GOUTARTHIRITIS DIDUSUN SUMBER BENDO DESA SUMBER TEBU BANGSAL MOJOKERTO - Monalisa Niken Kumalasari; Dwiharini Puspitaningsih; Siti Rachmah (MEDICA MAJAPAHIT, 2024)
Gout Arthritis is an inflammatory joint disease caused by high levels of uric acid in the blood, which is characterized by the accumulation of monosodium urate crystals in or around joints in the form of uric acid tophi. The design used in this study was case study to explore the problem of family nursing care for the elderly with Gout Arthritis. The process of family nursing care with 2 respondents with a history of goutarthiritis starting from August to September. With a nursing care approach that included assessment, nursing diagnoses, planning, implementation and evaluation. The results of the assessment on both clients found the same complaint, namely pain in the knee joints of the right and left legs. In client 1 the uric acid level was 7.2 mg/dl and in client 2 it was 10.2 mg/dlFamily nursing care for goutarthiritis patients was able to help clients in efforts to reduce uric acid levels after warm ginger compress therapy and proper diet for goutarthiritis. Families and clients was able to carry out and apply nursing care independently to family members who suffer from gout by applying regular health checks.